Doing time together : love and family in the shadow of the prison - Comfort, Megan (University of Chicago Press, 2008)
By quadrupling the number of people behind bars in two decades, the United States has become the world leader in incarceration. Much has been written on the men who make up the vast majority of the nation?s two million inmates. But what of the women they leave behind? Doing Time Together vividly details the ways that prisons shape and infiltrate the lives of women with husbands, fiancés, and boyfriends on the inside. Megan Comfort spent years getting to know women visiting men at San Quentin State Prison, observing how their romantic relationships drew them into contact with the penitentiary. T.